2022
DOI: 10.1038/s41598-022-23464-7
|View full text |Cite
|
Sign up to set email alerts
|

Restricted cafeteria feeding and treadmill exercise improved body composition, metabolic profile and exploratory behavior in obese male rats

Abstract: The aim of this study was to evaluate, in male Long-Evans rats, whether a restricted-cafeteria diet (CAFR), based on a 30% calorie restriction vs continuous ad libitum cafeteria (CAF) fed animals, administered alone or in combination with moderate treadmill exercise (12 m/min, 35 min, 5 days/week for 8 weeks), was able to ameliorate obesity and the associated risk factors induced by CAF feeding for 18 weeks and to examine the changes in circadian locomotor activity, hypothalamic–pituitary–adrenal (HPA) axis fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 80 publications
(129 reference statements)
0
7
0
Order By: Relevance
“…The improvement in biochemical parameters, such as lipoprotein concentrations and profiles were not metformin specific, whereas the glucose tolerance test did not improve in either intervention. Indeed, a recent study showed that rats fed on a calorie-restricted cafeteria diet (30% caloric restriction) did not have decreased circulatory levels of glucose, triglycerides, LDL-cholesterol, and HDL-cholesterol compared to those rats fed on a cafeteria diet without caloric restriction [ 46 ]. Thus, these results suggest that the beneficial effects we observed in mice subjected to the dietary intervention were mediated by the diet change and not by caloric restriction per se.…”
Section: Discussionmentioning
confidence: 99%
“…The improvement in biochemical parameters, such as lipoprotein concentrations and profiles were not metformin specific, whereas the glucose tolerance test did not improve in either intervention. Indeed, a recent study showed that rats fed on a calorie-restricted cafeteria diet (30% caloric restriction) did not have decreased circulatory levels of glucose, triglycerides, LDL-cholesterol, and HDL-cholesterol compared to those rats fed on a cafeteria diet without caloric restriction [ 46 ]. Thus, these results suggest that the beneficial effects we observed in mice subjected to the dietary intervention were mediated by the diet change and not by caloric restriction per se.…”
Section: Discussionmentioning
confidence: 99%
“…Training was performed in a treadmill (Columbus instruments, Columbus, OH, USA) as reported in [ 44 ] with some modifications.…”
Section: Methodsmentioning
confidence: 99%
“…Analysis of serum samples was performed as in [ 44 ]. Briefly, enzymatic colorimetric kits were used for the determination of serum total cholesterol, triglycerides, and glucose (QCA, Barcelona, Spain).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations